Effects of varying condensed distillers solubles, drying, and cooling temperatures on glass transition temperature of distillers dried grains - Rosentrater,Kurt A.; Muthukumarappan, K.; Bhadra, Rumela (My University, 2011)
Distillers dried grains with solubles (DDGS), a coproduct of ethanol fuel production, is used as an animal feed and often must be transported long distances. DDGS flowability problems often create nuisance in storage and transportation. Materials above the glass transition temperature (Tg) can exist in a “rubbery state,”’ which is often responsible for particle agglomeration and caking. This study investigated the effects of varying condensed distillers solubles (CDS) (10, 15, and 20%, wb), drying (100, 200, and 300°C), and cooling temperature (–12 and 35°C) levels on the Tg of DDGS. Tg ranged from 34 to 58°C and 41 to 59°C for cooling temperatures of –12°C and 35°C, respectively. Tg data were used to develop an overall regression model, which yielded a predictive model with R² of 0.74 and SEM of 3.16. Using this model, optimum drying and cooling temperatures were determined. These conditions may be used to reduce flow problems.
Keywords: Caking; Distillers dried grains with solubles (DDGS); Drying; Flowability